PREVALENCE OF INVASIVE PARTHENIUM WEED IN DISTRICT HAFIZABAD, PAKISTAN - T. Riaz; A. Javaid (Journal of Animal and Plant Sciences, 2010)
Surveys of waste and grazing lands from 10 localities of the district Hafizabad were undertaken during March-April, 2009 to study the distribution of an alien invasive weed parthenium (Parthenium hysterophorus L.) in comparison of the weeds of the area. A total of 67 weed species belonging to 25 angiospermic plant families were found growing in the district. Parthenium was found to be growing in nine out of ten studied sites exhibiting 90% prevalence. The absolute frequency of occurrence of parthenium was 51%. Out of 67 recorded weed species in the area, only 14 weeds showed absolute frequency of 50% or above including parthenium. Parthenium was found among the densely populated weed species with absolute density of 1.55. Only 7 weed species namely Ageratum conyzoides L. Cichorium intybus , Cirsium arvense (L.) Scop., Sueda fruticosa Forsk., Cenchrus pennisetiformis Hochest, Cynodon dactylon Pers., Dicanthium annulatum Stapf., and Rumex dentatus L in the studied area showed absolute density greater than parthenium. The present study concludes that parthenium is rapidly colonizing waste lands of district Hafizabad. Urgent efforst are necessary to control its further spread in the area.
Keywords: Alien weed; Hafizabad; Parthenium hysterophorus